Thidiazuron Improved Aglaonema ‘Ruby’ Microshoot Multiplication for Mass Production and Microfloriculture Development - Allya Alifia Purbaya; Rendie Prasetyo; Siti Samiyarsih; Sugiyono (Jurnal Biodjati, 2025)
Aglaonema 'Ruby' is a hybrid Aglaonema with a dominant green leaf pattern and a red accent in the middle. This cultivar is widely cultivated and in great demand, and it can potentially be used in micro floriculture development. Conventional Aglaonema propagation through stem cuttings can only produce 1-3 shoots. Therefore, the in vitro culture method is proposed. The objectives of this study were to evaluate the effect of three synthetic cytokinins (BAP, Kinetin, and TDZ—the latter being a phenylurea derivative with cytokinin-like activity) and concentrations on the multiplication of Aglaonema 'Ruby' microshoot. The research has been carried out experimentally using a split-plot design. The main plot was cytokinin types, consisting of BAP, Kinetin, and Thidiazuron; the subplot was cytokinin concentrations at 0, 5, 10, 15, and 20 µM. The measured parameters include shoot emergence time, number of shoots, leaves, and shoot length. The data were analyzed using an analysis of variance (ANOVA) followed by Duncan's multiple range test at 95% confidence level. It can be concluded that the growth of Aglaonema 'Ruby' micro shoots was controlled by the type and concentration of cytokinin given. Thidiazuron was better than Kinetin and BAP in stimulating the growth of Aglaonema 'Ruby' microshoots. Cytokinin at 10 µM seemed to be effective in improving Aglaonema 'Ruby' micro shoots multiplication. Thidiazuron at 10 µM can increase the production of Aglaonema 'Ruby' shoot to support both mass production of seedlings and microfloriculture products. Further studies are needed to optimize shoot and root development to produce good plantlets, easing the subsequent acclimatization.